2016
DOI: 10.1080/09658211.2016.1208248
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration enhances later individual memory for emotional material

Abstract: Research on collaborative remembering suggests that collaboration hampers group memory (i.e., collaborative inhibition), yet enhances later individual memory. Studies examining collaborative effects on memory for emotional stimuli are scarce, especially concerning later individual memory. In the present study, female undergraduates watched an emotional movie and recalled it either collaboratively (n = 60) or individually (n = 60), followed by an individual free recall test and a recognition test. We replicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
41
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 50 publications
7
41
3
Order By: Relevance
“…Yaron-Antar and Nachson (2010) found collaborative inhibition when groups of Israeli students were tested on their memory of the details concerning the assassination of Israeli Prime Minister Itzhak Rabin. Similarly, collaborative inhibition has been observed in female undergraduates’ memory for a film clip depicting a fatal car accident (Bärthel, Wessel, Huntjens, & Verwoerd, in press; Wessel, Zandstra, Hengeveld, & Moulds, 2015). In contrast to these findings, a recent study found no evidence of collaborative inhibition when examining couples’ memory for the emotional scene of a play depicting rape and murder (Vredeveldt, Hildebrandt, & von Koppen, 2016).…”
mentioning
confidence: 76%
“…Yaron-Antar and Nachson (2010) found collaborative inhibition when groups of Israeli students were tested on their memory of the details concerning the assassination of Israeli Prime Minister Itzhak Rabin. Similarly, collaborative inhibition has been observed in female undergraduates’ memory for a film clip depicting a fatal car accident (Bärthel, Wessel, Huntjens, & Verwoerd, in press; Wessel, Zandstra, Hengeveld, & Moulds, 2015). In contrast to these findings, a recent study found no evidence of collaborative inhibition when examining couples’ memory for the emotional scene of a play depicting rape and murder (Vredeveldt, Hildebrandt, & von Koppen, 2016).…”
mentioning
confidence: 76%
“…The degree of RSD experienced by a collaborative group is mediated by a number of factors including its size and the social relationship of its members (Marion & Thorley, 2016). Importantly, those collaborative eyewitness memory studies that observed CI (Bärthel et al, 2017;Wessel et al, 2015) and those that did not (Vredeveldt et al, 2016; differed with respect to both factors. Group size matters, as larger groups are more prone to CI (e.g., Marion & Thorley, 2016;Thorley & Dewhurst, 2007).…”
Section: Collaborative Eyewitness Memory (Correct Recall)mentioning
confidence: 96%
“…A third, non-RSD related, difference between those collaborative eyewitness memory studies that observed CI and those that did not, that may have contributed to their conflicting findings, was their study-test delays. The two studies that found evidence of CI had a 5-min study-test delay only (Bärthel et al, 2017;Wessel et al, 2015) whereas those that found no evidence of CI had study-test delays exceeding 15 min (Vredeveldt et al, 2016(Vredeveldt et al, , 2017. This is important as it has been demonstrated that CI is present during experiments that have study-test delays of up to 15 min (Takahashi & Saito, 2004) but disappears in experiments with longer study-test delays of 2 hrs (Congleton & Rajaram, 2011), 24 hours (Abel & Bäuml, 2017), and 1 week (Takahashi & Saito, 2004).…”
Section: Collaborative Eyewitness Memory (Correct Recall)mentioning
confidence: 96%
See 2 more Smart Citations